MT1G promotes iron autophagy and inhibits the function of gastric cancer cell lines by intervening in GPX4/SQSTM1 - Kaiqiang Meng; Jian Song; Fan Qi; Jiamin Li; Zhichao Fang; Liang Song (Scientific Reports)
Abstract Gastric cancer (GC) is the fifth most common cancer and the third most common cause of cancer death globally, with high invasiveness, high recurrence rate, and poor prognosis. Multiple studies have shown that Metallothionein-1G (MT1G) is closely associated with oxidative stress, ferroptosis, and autophagy. However, the role and potential mechanisms of MT1G in GC have not been fully elucidated. This study aims to explore the biological functions and regulatory mechanisms of MT1G in GC. Perform bioinformatics analysis using the TCGA database to investigate the expression of MT1G in GC. RT-qPCR and Western blot were used to detect the expression of MT1G, ferroptosis related proteins, autophagy related proteins and ARNTL clock autophagy related proteins in Hgc27, MKN45 and AGS cell lines. Exploring the biological functions of MT1G overexpressing GC cell lines through wound healing and transwell experiments. Use specific fluorescence probes to examine mitochondrial membrane potential and Fe2+ fluorescence intensity. Using immunoprecipitation analysis (CO-IP) to elucidate the association between GC cell lines GPX4, SQSTM and ARNTL. Use flow cytometry to detect ROS expression. Observation of autophagy related morphological changes in cells using transmission electron microscopy. Compared with gastric mucosal cell lines, the expression of MT1G is decreased in three gastric cancer cell lines (Hgc27, MKN45 and AGS). Overexpression of MT1G inhibits the proliferation, migration, and invasion functions of GC cells, reduces SOD and GSH content, increases MDA content, cause the mitochondrial membrane potential to weaken and promote the transformation of JC-1 aggregates to JC-1 monomer, increases Fe2+, affects ROS, and reduces GPX4 and SLC7A11 protein expression, promoting ferroptosis. Overexpression of MT1G promotes the transformation of LC3B I to LC3B II, reduces SQSTM1 protein expression, and leads to the appearance of more autophagosomes and autolysosomes at low magnification. At high magnification, mitochondrial autophagy, endoplasmic reticulum autophagy, lipid droplet autophagy, and wrinkled mitochondrial cristae are observed, promoting autophagy. Overexpression of MT1G inhibits GPX4, thereby affecting SQSTM1 as a vector to promote ARNTL autophagy and EGLN2, promoting ARNTL clock autophagy through the GPX4/SQSTM1 axis. Our research findings elucidate that overexpression of MT1G promotes iron autophagy centered around ARNTL in GC cells via the GPX4/SQSTM1 axis, thereby inhibiting GC cell function and providing a new molecular mechanism and therapeutic target for the development of GC.